Ultrathin TiO2 Coatings via Atomic Layer Deposition Strongly Improve Cellular Interactions on Planar and Nanotubular Biomedical Ti Substrates - Čapek, Jan; Sepulveda Sepulveda, Lina Marcela; Báčová, Jana; Rodriguez Pereira, Jhonatan; Zazpe, Raúl; Čičmancová, Veronika; Nývltová, Pavlína; Handl, Jiří; Knotek, Petr; Baishya, Kaushik; Sopha, Hanna Ingrid; Brůčková, Lenka; et al. (American Chemical Society, 2024)
This work aims to investigate the chemical and/or structural modification of Ti and Ti-6Al-4V (TiAlV) alloy surfaces to possess even more favorable properties toward cell growth. These modifications were achieved by (i) growing TiO2 nanotube layers on these substrates by anodization, (ii) surface coating by ultrathin TiO2 atomic layer deposition (ALD), or (iii) by the combination of both. In particular, an ultrathin TiO2 coating, achieved by 1 cycle of TiO2 ALD, was intended to shade the impurities of F- and V-based species in tested materials while preserving the original structure and morphology. The cell growth on TiO2-coated and uncoated TiO2 nanotube layers, Ti foils, and TiAlV alloy foils were compared after incubation for up to 72 h. For evaluation of the biocompatibility of tested materials, cell lines of different tissue origin, including predominantly MG-63 osteoblastic cells, were used. For all tested nanomaterials, adding an ultrathin TiO2 coating improved the growth of MG-63 cells and other cell lines compared with the non-TiO2-coated counterparts. Here, the presented approach of ultrathin TiO2 coating could be used potentially for improving implants, especially in terms of shading problematic F- and V-based species in TiO2 nanotube layers.
Ultratenké povlaky TiO2 nanášené prostřednictvím depozice atomové vrstvy silně zlepšují buněčné interakce na planárních a nanotubulárních biomedicinálních Ti substrátech.
Keywords: TiO2 nanotube layers; Ti foils; Ti-6Al-4V alloy; atomic layer deposition; cellproliferation; MG-63 cells; Vrstvy nanotrubiček TiO2; Ti fólie; slitina Ti-6Al-4V; depozice atomové vrstvy; buněčná proliferace; buňky MG-63